Varicella zoster meningitis: an atypical case of zoster reactivation in immunocompetent young adult. (5th January 2018) - Khaliq, Muhammad Farhan; Kochar, Tanureet; John, Molly
Abstract : Varicella virus is a neurotropic virus that can reactivate later in life to cause zoster or shingles. Typically, it affects elderly, immunocompromised population. We report an unusual case of an immunocompetent young adult presenting with occipital headache and zoster rash, without preherpetic and postherpetic neuralgia, who was diagnosed with varicella meningitis on Polymerase chain reaction (PCR). He was treated with intravenous acyclovir and later discharged on famciclovir. Diagnosis of varicella meningitis is difficult in the absence of typical features of zoster rash and requires high index of suspicion. Rapid diagnostic tests including varicella PCR and antithecal antibody testing can help in the confirmation of varicella zoster meningitis.